A avaliação na educação infantil do município de Tocantinópolis/TO: detalhes de uma pesquisa - Ferré, Cislany Nobres da Almeida (Universidade Federal do Tocantins, 2020)
The present work has the objective of studying the evaluative process in early childhood education and its main objective is to understand the limits and possibilities of evaluation in the early childhood education between the pedagogical and legal presuppositions and the challenges in the teaching practice of pedagogues that work in the infantile education of the municipality of Tocantinópolis -TO. For the development of the research we will use a qualitative approach with bibliographical field research, we will use as data collection technique the documentary analysis of the accompanying notebooks and the evaluation form used by the teachers, and we will make an interview with teachers. For the field of research we will choose a class of day care and another one of preschool. The authors of this paper are based on the literature on the Brazilian Constitution of 1988, the Law on Guidelines and Bases of Law, National Education Guidelines, the National Curriculum Guidelines for Early Childhood Education of 1998/2009 and the National Curriculum Framework for Early Childhood Education. It is hoped that the work can contribute to the understanding of the best conception and process of evaluating children's education, as well as their challenges, limits andpossibilities.